Technology in the British Industrial Revolution. Issue 4 (April 2016) - Tomory, Leslie
Abstract: Technology and technological innovation has been one of the crucial features of the historiography of the Industrial Revolution. In the early nineteenth century, this focus on the "machinery question", or the effects that machines had on the condition of labourer. Around 1900 academic historians began to explore the nature and causes of technological innovation, with Max Weber's thesis being the most influential. In the postwar period, optimistic assessment saw the technological creativity of the Industrial Revolution as crucial turning point in the history of Western economic growth. The period after 1970 has seen much broader fields of inquiry, including in product innovation, proto‐industrialization, and in industries outside the canonical group of cotton, iron, and steam engines.